Paroxysmal atrial fibrillation in cryptogenic stroke - Neha S Dangayach; Kevin Kane; Majaz Moonis (Dove Medical Press, 2011)
Neha S Dangayach1, Kevin Kane2, Majaz Moonis31Saint Vincent Hospital, 2University of Massachusetts Medical School, 3University of Massachusetts Memorial Health Center, Worcester, MA, USAIntroduction: Paroxysmal atrial fibrillation (PAF) is perhaps the most underdiagnosed mechanism of apparent cryptogenic stroke (CS). Various studies have shown that increasing the duration of monitoring can increase the diagnosis of PAF in CS.Methods: We compared demographic and risk factors for ischemic stroke across different TOAST (Trial of ORG 10172 in Acute Stroke Treatment) stroke subtypes to look for clinical differences between other subtypes and CS and subsequently performed periodic Holter monitoring and imaging studies in apparent CS patients.Results: Of the 298 patients with ischemic stroke, 17% had CS. Periodic holter monitoring enabled diagnosis of PAF in 29% of patients. Five of 51 patients with CS had recurrent ischemic stroke and all 5 were demonstrated as PAF on repeated Holter monitoring.Conclusions: Long-term periodic rhythm monitoring in patients with apparent CS showed PAF in a significant percentage of CS patients, which altered subsequent treatment.Keywords: cryptogenic stroke, atrial fibrillation, stroke of undetermined etiology